Analisis Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor di Kantor Samsat Soreang - Pratiwi, Reine Ajeng; Heriyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
As it is known that tax is a source of income and is an important aspect for the national development of a country, with the aim of increasing the welfare of a just and prosperous society. The issue of taxpayer compliance is an important issue throughout the world, both in developed and developing countries. The purpose of this study was to determine the factors that influence taxpayer compliance in paying motor vehicle tax at the Soreang Office. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out by means of interviews, observation, and documentation. The data analysis method used is data reduction, data presentation, and conclusion. The results show that taxpayer compliance in paying motorized vehicle taxes at the Soreang Samsat Office is quite good, but there are still some taxpayers who have not complied. This can be caused by several influencing factors such as understanding of the tax collection system, service quality factors, educational level factors, and income factors. In additional, there are two additional factors that can influence, including psychological factors of the taxpayer and also the habit of the taxpayer. Keyword : Taxpayer Compliance, Motor Vehicle Tax